The Effect Of Using Anticipation – Reaction Guide Strategy On Students’ Reading Comprehension In Recount Text At The Eighth Grade Of SMPN 3 Palembayan - Alvin Khaira; Merry Prima Dewi; Hilma Pami Putri; Widya Safitri (Lembaga Pengembangan Kinerja Dosen, 2023)
This Research was done due to several problems found: Students ability in reading were low, lack of interesting in reading, and students were difficult to comprehend the text. Anticipation Reaction Guide strategy is related to this problem because the Anticipation Reaction Guide is enabled strategy to help the students who may hold misconceptions regarding a specific concept based on the lesson in reading. Therefore, this research was to investigate the effect of using Anticipation Reaction Guide Strategy on Students’ Reading Comprehension. This research used quantitative method with quasi-experimental design by comparing two classes. The researcher used a cluster sampling technique because teacher recomendation and these class have similar characteristics. The total sample was 53 students of VIII 1 and VIII 2. The researcher used multiple test wich consisted of pre test and post test were applied in collect the data. Based on the data analysis used T- test Formula. The result from post test both of classes, it was t-obtained (2.73) was higher than the t-table (2.009). So it means that alternative hypothesis (Ha) was accepted while the null hypotesis (Ho) was rejected. So, it means that using anticipation-reaction guide strategy can help students to increase their reading comprehension.